2013
DOI: 10.1002/lt.23715
|View full text |Cite
|
Sign up to set email alerts
|

Inferior survival in liver transplant recipients with hepatocellular carcinoma receiving donation after cardiac death liver allografts

Abstract: The impact of ischemia/reperfusion injury in the setting of transplantation for hepatocellular carcinoma (HCC) has not been thoroughly investigated. The present study examined data from the Scientific Registry of Transplant Recipients for all recipients of deceased donor liver transplants performed between January 1, 1995 and October 31, 2011. In a multivariate Cox analysis, significant predictors of patient survival included the following: HCC diagnosis (P < 0.01), donation after cardiac death (DCD) allograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 28 publications
(63 reference statements)
5
58
0
Order By: Relevance
“…1 We agree with the authors that there are no hepatocellular carcinoma (HCC) recurrence data in the Scientific Registry of Transplant Recipients database; therefore, it was not possible to demonstrate that this was the cause of inferior survival observed in the HCC-donation after cardiac death (DCD) group. Although we gave early recurrence as a possible explanation for this inferior survival, we also discussed the idea that the use of DCD organs in patients with HCC may be a practice pattern used for patients who are felt to have greater factors for adverse risk.…”
supporting
confidence: 53%
“…1 We agree with the authors that there are no hepatocellular carcinoma (HCC) recurrence data in the Scientific Registry of Transplant Recipients database; therefore, it was not possible to demonstrate that this was the cause of inferior survival observed in the HCC-donation after cardiac death (DCD) group. Although we gave early recurrence as a possible explanation for this inferior survival, we also discussed the idea that the use of DCD organs in patients with HCC may be a practice pattern used for patients who are felt to have greater factors for adverse risk.…”
supporting
confidence: 53%
“…One previous study suggests an interaction between HCC and receiving a DCD allograft that leads to inferior survival. 24 However, the study is plagued by the limitations of registry-based data and absence of HCC recurrence data. Even though the authors provide an important observation, they are left to speculate on the reasons for the poorer outcomes for recipients with an HCC diagnosis when DCD allografts are used.…”
Section: Discussionmentioning
confidence: 99%
“…To date, utilization of DCD allografts in patients with HCC has not been examined extensively. One previously published paper examining the data from the SRTR database suggested that even after adjustments for the inherent inferiority observed in DCD allografts as well as other known risk factors, there was an inferior survival for HCC recipients of DCD allografts versus recipients of DBD allografts (8). Early HCC recurrence in the DCD group was postulated as one potential explanation for the observed difference in survival between the DCD and DBD groups.…”
Section: Discussionmentioning
confidence: 99%
“…Survival difference remained even after adjustments for the inherent inferiority observed in DCD allografts as well as other known risk factors (8). While it was postulated that the difference in survival could reflect an increased rate in the recurrence of HCC, the SRTR database does not contain specific data related to recurrence.…”
Section: Introductionmentioning
confidence: 99%